Modified ground calcium carbonate mineral powder using in asphalt concrete: modification mechanism characterization at macro and micro levels - Zhang, Zijun; Yan, Wenda (Frontiers in Materials, 2023)
The study investigated the modification mechanism of modified ground calcium carbonate (GCC) mineral powder using in asphalt concrete. Two types of Titanate coupling agents, namely K38S (TCA-K38S) and 201 (TCA-201), as well as sodium stearate coupling agent, were adopted to prepare modified GCC. The optimized preparation process was obtained through the orthogonal test. Two kinds of modified GCC were preferably selected to prepare asphalt concrete according to modification mechanism characterization, their performance was analyzed and evaluated at macro and micro levels. The study results show that, the optimal scheme of sodium stearate modified GCC is modification temperature of 80℃, modification time of 50 mins, modifying agent dosage of 2.0%. The crystal structure of GCC remains unchanged after modification, with the original lattice structure being maintained. TCA-201 and sodium stearate exhibit better coating properties than that of TCA-K38S. The contact angles of TCA-201 and sodium stearate modified GCC are larger than that of TCA-K38S modified GCC. The in-service performance of AC-13C asphalt concrete modified with sodium stearate is found to be superior to that of TCA-201 modified AC-13C asphalt concrete. Compared with the unmodified AC-13C asphalt concrete, the Marshall modulus, residual stability, freeze-thaw splitting strength ratio, and maximum flexural tensile strain of sodium stearate modified AC-13C asphalt concrete are increased by 54.55%, 2.73%, 10.47%, and 26.41% respectively.